Long‐term clinical outcomes of dogs with single congenital extrahepatic portosystemic shunts attenuated with thin film banding or ameroid ring constrictors. Issue 3 (22nd January 2020) - Otomo, Aki; Singh, Ameet; Jeong, Junemoe; Dobberstein, Rachel; Lundhild, Alexandra; Peter, Elyse; Brisson, Brigitte; Oblak, Michelle; Milovancev, Milan
Abstract: Objective: To compare long‐term clinical outcomes of dogs with single congenital extrahepatic portosystemic shunts (CEHPSS) treated with thin film banding (TFB) consisting of polyolefin fiber or ameroid ring constrictor (ARC) placement in dogs. Design: Retrospective, two‐center clinical study. Animals: Client‐owned dogs (n = 123) with single CEHPSS undergoing gradual attenuation via TFB (n = 85) or ARC (n = 38). Methods: Medical records of dogs with CEHPSS were reviewed. Follow‐up data were collected from the referring veterinarian and/or owner via standardized questionnaire. Data were analyzed to compare short‐term mortality rate and long‐term outcome (>6 months). Results: Dogs in the TFB group were older than dogs in the ARC group (median age, 19 vs 12 months, respectively; P = .01). There was no difference in survival to discharge between dogs in the TFB (81/85 [95.3%]) and ARC (37/38 [97.4%]; P  > .99) groups. Preoperative levetiracetam was more frequently administered to dogs treated with TFB (64/85 [75.3%]) than to dogs treated with ARC (15/38 [39.5%;] P = .0002). Postoperative seizures were reported in 10 (8.1%) dogs; their prevalence did not differ between dogs treated with TFB (9/85 [10.6%]) and dogs treated with ARC (1/38 [2.6%]; P = .17). Median follow‐up time for dogs treated with TFB (58.0 months, range 8‐130) and ARC (63.3 months, range 7‐138; P = .24) did not differ. Conclusion: Gradual attenuation of a single CEHPSS with either TFB or ARC resulted in similar long‐term clinical outcomes and low postoperative morbidity and mortality rates. Clinical significance: Thin film banding (polyolefin fiber) offers an alternative leading to clinical outcomes similar to ARC in dogs with single CEHPSS.